The Humanitarian Supply Chain Assessment Tool (HumSCAT). Issue 2 (24th September 2019) - Banomyong, Ruth; Julagasigorn, Puthipong; Varadejsatitwong, Paitoon; Piboonrungroj, Pairach
Abstract : Purpose: An understanding of the "AS-IS" stage of a relief operation is the basis for further action in humanitarian supply chain management. The purpose of this paper is to develop a toolbox called the Humanitarian Supply Chain Assessment Tool (HumSCAT). This toolbox is comprised of a set of basic tools which can be classified into each phase of disaster relief. Design/methodology/approach: The HumSCAT is proposed by paralleling frequently used tools in commercial supply chains with the objectives and characteristics of relief phases. A case study was used to validate the HumSCAT along with six tools provided in the preparation phase. Findings: The HumSCAT consists of seven tools in the preparation phase, nine tools in the response phase and ten tools in the recovery phase. The case study illustrates how to use the HumSCAT and the six tools. The latter were found to be useful for improving the relief chain. Research limitations/implications: The list of tools is not exclusive. Other tools might be applicable as long as they meet the objectives and characteristics of the phase. A tool should be adjusted accordingly to the contexts. Tools in other phases should be validated in future research. Practical implications: The HumSCAT may serve as a reference toolbox for practitioners. Its output can be used for further designing of the "TO-BE" status of humanitarian relief chains. Originality/value: The HumSCAT is proposed as a toolbox for academics and practitioners involved in humanitarian supply chains.